MODEL PENGATURAN HUKUM PIDANA TERHADAP PENGGUNA JASA PEKERJA SEKS KOMERSIAL DI INDONESIA - Leni Fuji Lestari; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Prostitution is a job that a person who acts as an intermediary or service provider (pimps), commercial sex workers, and service users themselves. Commercial sex work is not only carried out by people who do it down the middle to meet the necessities of life, in fact, recently we see and listen to the news that public figures, though there have been many who undergo job These just to get more money. If seen from the legitimacy of the law, the service user can not be subject to criminal terbenturnya because the law enforcement in Indonesia with the legal principle of "nullum delictum nulla poena sine lege poenali pravia" which means there is no one the delik can are convicted without the rules in advance, plus more because of legal arrangements which exist only as in the Bylaw area which is not binding on all over the place in the country of Indonesia. At this time, the application of the principle of legality is in an alarming stage where law enforcers often use criminal law based on the principle of the legality of a rigidly based on legislation. The purpose of writing this thesis, namely: first, the criminal sanctions Against users of the services of commercial sex workers in Indonesia. Second, the Ideal Settings Against service users of commercial sex workers in Indonesia. This type of research can be classified in types of normative research, because in this study the author discusses about legal principles concerning the rule of law for the service users of commercial sex workers. From the results of the research there were two basic problems that can be inferred. First, according to positive law in Indonesia, there has been no criminal sanctions which ensnare the users of the services of commercial sex workers. This is because the book of Criminal law in use today is still a legacy of the colonial Netherlands East Indies. In the CRIMINAL CODE currently does not yet have specific rules governing the crime of prostitution. The second, not the existence of the ideal settings and difficulty of lawmen to trapping the perpetrators of prostitution is also caused due to the principle of the legality of this led law enforcers difficult moves to eradicate the practices of the duty undergo prostitution. The author's suggestion, first, the Expected criminal sanctions that were previously just to pimp or procurer of course, in the time to come may be subject also to users of commercial sex workers service workers even itself. Second, the ideal Setting to establish criminal sanctions against commercial sex workers service users can be realized with the renewal of the book of the law of criminal law. Keywords: Legal Arrangements-Prostitution-Law Updates